Exploring Apoptotic Pathways in Cancer: Computational Investigation of Plectronia parviflora and Agave cantala extracts - Cheruku, Sandeep Reddy; Shaheedha, S.M.; .Gopi, G; Thacheril, Anugeetha; Reddy G, Ramachandra; Begum, M. Shamshath (Journal of Neonatal Surgery, 2025)
Cervical and breast cancer are significant global health concerns, demanding novel therapeutic strategies. This study evaluates the cytotoxic potential of hydro alcoholic extracts (1:1 water and alcohol) of Plectronia parviflora and Agave cantala, along with their isolated fractions (IF-PL and IF-AC), on HeLa cell lines. We assessed cellular viability using the MTT assay, apoptotic induction via flow cytometry, morphological changes using the Trypan Blue assay, and apoptosis-related marker modulation through Western blotting. Our findings indicate dose-dependent reductions in cell viability, particularly with the hydroalcoholic extracts, IF-PL, and IF-AC at concentrations of 45.75 µg/ml and 54.48 µg/ml. Notably, these agents significantly induce both early and late apoptosis, confirmed by flow cytometry analysis. Treated cells displayed typical morphological alterations, including condensed nuclei, cytoplasmic shrinkage, and denatured cell walls, emphasizing the cytotoxicity of the extracts. Western blot analysis revealed a significant increase in caspase-3 activity and a shift in the balance between pro-apoptotic BAX and anti-apoptotic BCL-XL proteins. Additionally, upregulation of IL-10 suggested an associated inflammatory response. These findings highlight the potential of Plectronia parviflora and Agave cantala extracts, along with their isolated fractions, as promising candidates for cancer therapy. Their cytotoxic effects, apoptosis induction, modulation of apoptosis-related markers, and morphological changes support their role as potential alternatives to conventional chemotherapy. Further exploration of their mechanisms and clinical applications is essential, offering potential for future advancements in cancer treatment. Additionally, in silico studies revealed promising interactions between the extracts and cancer targets, further supporting their therapeutic potential.